2022
DOI: 10.1111/jopr.13615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Cycling on the Flexural Strength and Hardness of New‐Generation Denture Base Materials

Abstract: To evaluate the flexural strength and Vickers microhardness of different CAD-CAM denture base materials. Materials and methods: Sixty rectangular specimens (64 × 10 × 3.3 ± 0.2 mm) were fabricated from 3 different denture base materials (G-CAM, Graphene-reinforced polymethylmethacrylate, GC), Ivotion Base (Prepolymerized polymethylmethacrylate, IV), and Denturetec (3D-printed resin, DT) either by using additive (DT) or subtractive manufacturing (IV and GC). Specimens of each group were divided into 2 subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
1
27
4
Order By: Relevance
“…investigated. 10,12,13,[16][17][18][19] A previous study on the R a of GSM has reported that it had similar values to those of tested prepolymerized PMMA. 19 GSM was also reported to have microhardness that was either similar to or higher than prepolymerized PMMA.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…investigated. 10,12,13,[16][17][18][19] A previous study on the R a of GSM has reported that it had similar values to those of tested prepolymerized PMMA. 19 GSM was also reported to have microhardness that was either similar to or higher than prepolymerized PMMA.…”
Section: Discussionmentioning
confidence: 64%
“…Even though the number of studies on the optical properties of GSM is limited, 14,20 its mechanical properties have been broadly investigated 10,12,13,16–19 . A previous study on the R a of GSM has reported that it had similar values to those of tested prepolymerized PMMA 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations